Language Diversion: Student’s Use of Slang as Everyday Language - Lovna Akter (UICELL, 2022)
The purpose of this study is to determine how university students feel about the use of slang. Even though slangs almost, always have negative connotations, it can be argued that they are not always used to offend people. Slangs are also used to express all kinds of emotions ranging from joy to grief, happiness to depression, pleasure to frustration. Mixed method was followed and a total number of hundred students from two private universities were selected as samples using the convenience sampling technique. The statistics demonstrated that the use of slang has become indispensable. On a conclusive note, the analysis of the data suggests, despite all the negative connotations, students use slangs inevitably as everyday language. Keywords: Slang; language; student; expression